2012
DOI: 10.3892/or.2012.2010
|View full text |Cite
|
Sign up to set email alerts
|

Yes is a central mediator of cell growth in malignant mesothelioma cells

Abstract: The constitutive activation of the Src family kinases (SFKs) has been established as a poor prognostic factor in malignant mesothelioma (MM), however, the family member(s) which contribute to the malignancy have not been defined. This study aimed to identify the SFK member(s) contributing to cell growth using RNA interference in various MM cell lines. Silencing of Yes but not of c-Src or Fyn in MM cells leads to cell growth suppression. This suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
1
23
0
2
Order By: Relevance
“…20) Moreover, we have reported that Yes but not c-Src is a central role in determining malignancy of MM cells. 14) Overall, it is considered that the activation of Yes/HIF-2α by CoCl 2 treat- ment is associated with VEGF overexpression in H2452 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20) Moreover, we have reported that Yes but not c-Src is a central role in determining malignancy of MM cells. 14) Overall, it is considered that the activation of Yes/HIF-2α by CoCl 2 treat- ment is associated with VEGF overexpression in H2452 cells.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Yes, a member of SFK has been reported to be a central mediator of cell growth in MM cells. 14) As the VEGF and HIF pathways are intertwined to promote angiogenesis and tumor growth, targeting Yes/HIF-2α/VEGF signal pathway may represent a viable anticancer therapeutic target for MM.…”
mentioning
confidence: 99%
“…Additionally, we revealed that Yes, a member of the Src family kinases, is a central mediator in MM cell growth [24], and showed that T3E inhibits hypoxia-induced VEGF secretion via Yes signaling in MM cells [25]. Furthermore, to identify the main signal molecule involved in the anti-MM effect of T3E, comprehensive gene expression analysis was carried out using a DNA microarray.…”
Section: Discussionmentioning
confidence: 99%
“…There was downregulation of Lats2 , a downstream regulator of the Hippo pathway, which is implicated in the pathogenesis and promotion of human mesothelioma along with TGFβ (Fujii et al 2012). The oncogenes MafB and Yes were consistently upregulated in mesotheliomas from both vehicle control and VDC-exposed rats, which are mediators responsible for cell proliferation in human malignant mesotheliomas (Gordon et al 2005; Sato et al 2012). The gene expression of epithelial cell adhesion molecule ( Epcam ), a transmembrane p-glycoprotein that has multiple roles in cell signaling, migration, proliferation, and differentiation (Patriarca et al 2012), was upregulated in rat mesotheliomas.…”
Section: Discussionmentioning
confidence: 99%